Efficient Transport and Biotransformation of Dipeptide-like Tyrosine/Phenylalanine-Conjugated Phenolic Amide Esters in THP-1 Cells and PBMCs: A Potential Means for Transporting Compounds Inside Monocytes/Macrophages - Park, Jae B. (Current Nutraceuticals, 2022)
Background: Recent studies suggest that dipeptide-like tyrosine/phenylalanine-conjugated phenolic amide compounds may contain several biological activities, including anti-inflammatory activity. However, there is currently no information about their transport and biotransformation in monocytes/macrophages involved in inflammation process. Objective: The objective of this study was to investigate cell transport and biotransformation of the phenolic amides and esters in monocyte/macrophage-like cells. Methods: Cell transport and biotransformation of the phenolic amides and esters (N-coumaroylphenylalanine, N-caffeoylphenylalanine, N-feruloylphenylalanine, N-coumaroyltyrosine, N-caffeoyltyrosine, N-feruloyltyrosine, and their O-methyl esters) were investigated in THP-1 cells and PBMCs using HPLC, cellular, and kinetics methods. Results: In THP-1 cells, the phenolic amides were not transported significantly, but their O-methyl esters were transported significantly (P < 0.02). Also, the transport of the esters was found to be sodium-independent and pH-dependent. Among the tested esters, N-feruloylphenylalanine-O-methyl ester showed the highest uptake (Km of 25 µM), and the uptake was inhibited by PepT1/2 substrate and blocker (GlySar and enalapril) in THP-1 cells. Particularly, enalapril competitively inhibited the uptake with Ki of 560 µM. The data also showed that N-feruloylphenylalanine-O-methyl ester and N-feruloyltyrosine-O-methyl ester could be biotransformed into parent phenolic amides in THP-1 cells. Similarly, these ester compounds were also found to be transported and biotransformed in PBMCs. Conclusion: The data suggest that dipeptide-like tyrosine/phenylalanine-conjugated phenolic amide esters may be transported and biotransformed in THP-1 cells and PBMCs.
Keywords: PepT2